2006
DOI: 10.1021/ja057513w
|View full text |Cite
|
Sign up to set email alerts
|

Protein Ligand Design:  From Phage Display to Synthetic Protein Epitope Mimetics in Human Antibody Fc-Binding Peptidomimetics

Abstract: Phage display is a powerful method for selecting peptides with novel binding functions. Synthetic peptidomimetic chemistry is a powerful tool for creating structural diversity in ligands as a means to establish structure-activity relationships. Here we illustrate a method of bridging these two methodologies, by starting with a disulfide bridged phage display peptide which binds a human antibody Fc fragment (Delano et al. Science 2000, 287, 1279) and creating a backbone cyclic beta-hairpin peptidomimetic with 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 19 publications
1
75
1
Order By: Relevance
“…This is because the Fc-III peptide binds with relatively high affinity (the apparent dissociation constant K d is 30 nM) to the groove between the CH2 and CH3 domains of human IgG and shares common binding sites with Protein A. In addition, the Fc-III peptide has been used in studies of affinity enhancement (10) and artificial cell-surface antibody receptors (11).…”
mentioning
confidence: 99%
“…This is because the Fc-III peptide binds with relatively high affinity (the apparent dissociation constant K d is 30 nM) to the groove between the CH2 and CH3 domains of human IgG and shares common binding sites with Protein A. In addition, the Fc-III peptide has been used in studies of affinity enhancement (10) and artificial cell-surface antibody receptors (11).…”
mentioning
confidence: 99%
“…The energetic importance of Trp30 has been previously confirmed by alanine scanning mutagenesis (DDG > 2.0 kcal/mol) (DeLano et al, 2000). Furthermore, it has been reported that the orientation of the Trp30 aromatic ring critically affects the affinity (Dias et al, 2006). The alanine substitution of Met48 significantly reduced the affinity by more than 100-fold, which strongly indicates the importance of the direct support of the ring conformation.…”
Section: How the Assembled Segments Enhanced Functionmentioning
confidence: 74%
“…This 13-residue peptide needs structural stabilization by a disulfide bond for the binding function, and the loss of the disulfide bond causes a 1,760-fold affinity decrease (Table 1). We used an alanine-substituted mutant of Fc-III, termed Fc-III Ala, as a model of a low-function peptide for the following reasons: the three-dimensional structures of Fc-III (DeLano et al, 2000) and its chemically modified derivatives (Dias et al, 2006) have been determined, which allowed us to analyze at the atomic level how adaptive assembly enhanced the function; and the disulfide-bond deletion mutant is a suitable model for validation of adaptive assembly, since its purpose is to stabilize a structurally unstable peptide to generate a function-enhanced protein.…”
Section: Design Of Segment-based Librariesmentioning
confidence: 99%
“…Structure of the cyclic peptide 57, and its DKP analogue 58. of the loop into a β-hairpin geometry. One of these hairpininducing templates is the dipeptide D-Pro-L-Pro, extensively used by Robinson´s group [183][184][185][186][187][188], which is able to stabilize several attached loops in β-hairpin conformation. This template has been applyed to retain the β-hairpin geometry of cyclic peptide trypsin inhibitors, and of inhibitors of the binding of Protein A to a human antibody Fc fragment.…”
Section: Miscelaneous Examplesmentioning
confidence: 99%
“…Fc binding ligands may be of value for biotechnological applications, as replacement for recombinant proteins, such as Protein-A, in the affinity chromatography of therapeutic antibodies. A combination of phage display and peptidomimetic chemistry, directed to find peptides able to bind to this fragment, resulted in the disulfide bridged peptide FcIII [188]. The crystal structure of this peptide in complex with the Fc domain confirmed that FcIII is constrained into a β-hairpin conformation by the disulfide bridge.…”
Section: Miscelaneous Examplesmentioning
confidence: 99%